PEMBUATAN KOMPOS CAIR DARI SAMPAH ORGANIK RUMAH TANGGA DI KM 13 PONDOK MEJA - Afrida, Afrida; Heriyanti, Heriyanti; Utami, Andita (Jurnal Karya Abdi Masyarakat, 2017)
Waste management can not only depend on the role of government, but also required public participation. Public awareness of the importance of waste management should begin to be grown. In addition to reducing the risk of environmental pollution, waste management aims to produce something more useful. Inorganic garbage can be managed with recycling technology that can produce a wide variety of useful items. Meanwhile, organic waste or organic waste can be managed and used as liquid compost. Technology applied to the manufacture of liquid compost that is by using a microorganism that can accelerate the decomposition process of organic materials. Thus, the waste management efforts into something more useful can be realized. Liquid compost is more effective and efficient when applied to the leaves, flowers and stems than the growing media (except in the hydroponic method). Liquid organic fertilizer can serve as a stimulus to grow. Especially when the plants begin to sprout or when the change from vegetative to generative phase to stimulate the growth of fruits and seeds. Leaves and stems can absorb fertilizers applied directly through the stomata or pores that exist on its surface.